How bivocational church planters have operated in an Irish context - Montgomery, David J., 1963- (2013)
1 online resource (1 PDF (xv, 310 leaves)) : [2] maps; Typescript; Includes abstract; Thesis (D. Min.)--Covenant Theological Seminary, 2013; Bibliography: leaves 297-310